The Effect Of Health Education On Peer Group's Approach To Adolescent Readiness To Face Menarche - Prahardian Putri; Yolanda Alfurqonia Indani Putri; Pitri Noviadi; Yunike Yunike; Ira Kusumawaty (LAFADZ JAYA Publisher, 2022)
Menarche is a condition when a woman experiences her first menstruation. One way for young women to have the readiness to face menarche is to provide information about menstruation correctly. Information about menarche can be obtained from health education. This study sought to ascertain the impact of a peer group approach to health education on adolescent readiness to face menarche. This research was conducted using the queasy experimental method having a control group design that is non-equivalent. The sampling method in this study is a probability sampling technique with proportioned stratified random sampling. In this investigation, 92 samples were included in the sample size and using the Two Independent Sample Test with the Mann-Whitney U type, the Pearson Chi-square test, and the Continuity Correction test. The results of this study indicated by the p-value (0,000) and the results using the Pearson chi-square test and Continuity Correction show the results of insignificant relationships between ages (0.096), sources of information (0.529), parental education (0.267), parental employment (0.132), and family economic status (0.456) with adolescent teenagers' preparedness for menarche. So that the effect of a peer group approach to health education towards preparing adolescents for menarche at SDN 243 Palembang.